Pengaruh Literasi Keuangan Terhadap Perilaku Konsumtif Masyarakat Desa Majelis Hidayah, Kecamatan Kuala Jambi, Kabupaten Tanjung Jabung Timur - Roy Hambali; Arsa Arsa; Anzu Elvia Zahara (Al Itmamiy Jurnal Hukum Ekonomi Syariah (Muamalah), 2022)
This thesis is a study that examines the influence of financial literacy on consumptive behavior in the village community of Majelis Hidayah, Kuala Jambi District, Tanjung Jabung Timur Regency. The purpose of this thesis is to determine the effect of financial literacy on the consumptive behavior of the village community of Majelis Hidayah, Kuala Jambi District, Tanjung Jabung Timur Regency. In this study using quantitative methods with data collection techniques namely observation and questionnaire distribution in which the questionnaire itself is an instrument in collecting data. Then the validity and reliability tests were carried out to ensure the accuracy of each question on the questionnaire to be used in collecting data. After that, the classical assumption test was carried out in order to determine the accuracy of the data and hypothesis testing in the form of test (t), simple linear regression test and coefficient of determination test (R2).